(untitled) (Fiep Bulletin - online, 2016)
This article aimed to search the implications in the development of occupational diseases in the relations among Health, Labor and the Elementary School Physical Education Teacher’s Work Environment. The research is characterized as a literature review in books, articles, and laws from SCIELO database. The main findings point to the increased incidence of illness in work. The most frequent diseases are the Burnout Syndrome, Depression, Chronic Diseases and Injuries Noncommunicable, Skin Cancer, among others, generating in many cases the abandonment of the profession or early retirement, which allows us to infer that in our capitalist production model, the relationship among Health, Labor and Environment are unbalanced, in other words, occupational health is threatened in the current unfavorable conditions of work and environments.